The Translator’s Visible Touch in the First-person Narrative: On the Example of the Japanese Translation of Hyperion by Dan Simmons - Przybysz , Aleksandra (Silva Iaponicarum, 2024)
The translators have an ambiguous role in the process of a literary translation – they have to be as transparent as possible, though they must often interpret the text before translating it. In fact, they present their own dialogue with the author to the reader and thus, it is difficult for them to not influence a narrative with their presence (Venuti 1986: 182). Translators can, however, choose how and where they are visible. The purpose of this paper is to analyze the way a literary translator becomes visible to the reader through the translation. Three short stories – in first-person narrative – from the novel Hyperion by Dan Simmons and translated by Sakai Akinobu are discussed. The article focuses on the analysis of translator’s choices regarding vulgarisms and emotional load in a text generally, that influences the way the reader understands the text.